Spekulatív fikció, határmunkálatok, műfaji olvasás - Bárány, Tibor (Studia Litteraria, 2022)
A philosophical account of genre and of the criteria for genre-membership should explain at least five empirical facts: (i) genres may change over time, so genres have histories, (ii) membership in categories of genre is determined by a cluster of non-essential criteria, (iii) a work’s membership of a genre can affect its interpretation, and (iv) may significantly influence the aesthetic value we ascribe to it, (v) a one-to-many relationship occurs between works and genres, which is sometimes defined by conflicting principles (see hierarchies of genres, hybrid genres etc.). In this paper I examine how well some recent philosophical theories of genre can do this explanatory job – namely, Simon J. Evnine’s view of genres as traditions (i.e., temporally extended particulars), Gregory Currie’s conception of “genres for a community” and “dynamical genres”, Enrico Terrone’s cluster account of genres, and Catharine Abell’s Gricean theory of genres, according to which genre-membership is partly determined by the autor’s and audience’s common knowledge of the purpose characteristic of the genre.